Megjelölt zsidók meneteltetése Budapest utcáin 1944. október 17. (Hungary, 1944)
After the Arrow Cross takeover on October 15, 1944, armed resistance broke out in Népszínház Street, in an almost unique way in the capital, which was only defeated in a matter of days with German help. As a deterrent, on October 16, the Arrow Cross diverted hundreds of people from the nearby starred houses in front of the Tisza Kálmán square (now János Pál Pápa square) City Theater (today Erkel Theater). After being certified and looted, they had to spend the night in the equestrian track building (Tattersal) and then marched in various parts of the city for the next two days, a crowd of mostly women, the elderly and children.
Yellow Star Houses Film Program 2014
Keywords: Documentary films